Rzeczowniki z przyrostkiem -ota w Panu Tadeuszu Adama Mickiewicza (analiza słownikowa) - Szpiczakowska, Monika (Slavia Occidentalis, 2019)
The article is dedicated to a lexical analysis of adjectival nouns with the –ota suffix in Adam Mickiewicz’s Pan Tadeusz. Out of five nouns, viewed against the 19th century language norm, four are definitely archaisms. These are the words: ciemnota meaning <ciemność - darkness>, szczodrota (generosity) and some uses of the words cnota (virtue) and hołota (the poor and badly educated). On top of the noun ciemnota meaning <ciemność - darkness> which is a typical Easter Borderlands archaism, they should be traced back to the literary tradition. This is corroborated by the fact that the poet used them in an informed way to make the text sound like Old Polish. Therefore, with respect to the function and the archaic origin, the nouns with the –ota suffix in the text of “Pan Tadeusz” can be divided into two groups: stylistic archaisms which come from the literary tradition (szczodrota, partly cnota and hołota) plus systemic archaisms which belong to Mickiewicz’s idiolectal system (ciemnota meaning <ciemność - darkness>).